Epidemiology Of Influenza A Viruses In The Avian And Swine Populations In Peninsular Malaysia - Ramiah, Suriya Kumari (2008)

(untitled)
Avian influenza (AI) that has emerged from animal reservoirs represents one of the greatest concerns to public health. To date, 16 hemagglutination subtypes and nine neuraminidase subtypes are found in many different combinations. The general objective of this study is to describe the epidemiology of influenza A viruses in the animal population in Malaysia. The specific objectives of the study are to describe the pattern and geographical distribution occurrence of the various AI strains in the avian species in Peninsular Malaysia based on retrospective examination of records and data from disease surveillance conducted in previous years, to identify, describe and determine the risk factors of the influenza strains circulating in the pig populations, and detect and isolate the influenza virus in the pigs, and molecularly characterised the strains that were isolated. A descriptive analysis was performed on the AI data based on the surveillance that was conducted by the Department of Veterinary Services (DVS) between 2000 to ii 2005. A three-page questionaire was developed and administered to the participating states. Only Kedah, Perak, Pulau Pinang, Johor, Negeri Sembilan and Pahang responded to the questionnaire. Data that were collected were compared to the total number of poultry farms and avian related establishments in each state. The sample size for each state was calculated using the formula given by Dahoo et al (2003) and using FreeCalc software. Using the assumptions of 0.5% prevalence and confidence level of 95%, neither highly pathogenic AI nor low pathogenic AI has been detected in samples.A cross-sectional study was carried out to determine the seroprevalence of H1N1 and H3N2 swine influenza virus (SIV) and the risk factors of SIV in the pig population. Between May and August 2005, 41 randomly selected farms were visited where a total of 727 serum samples from 4 to 6-months-old pigs were collected. Each subtypes of H1N1 and H3N2 were detected at 17 farms (41.4%). Eight-nine animals (12.2%) and 88 animals (12.1%) were seropositive for H1N1 and H3N2 respectively. Using binary logistic regression, four common risk factors were identified for SI H1N1 and H3N2: Farm size, farms that import pigs or purchase pigs from elsewhere, farms where animals such as cats were observed and farms that were closely located to another pig farm. The study proceeds with virus detection and isolation from randomly selected samples that were seropositive for H1N1 or H3N2. Allantoic fluids were collected from inoculated eggs and tested using hemagglutination test, One-Step Real time Polymerase Chain Reaction (RRT-PCR) and Conventional Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). All samples were tested negative using HA and RRT-PCR. The failure to isolate the H1N1 and H3N2 viruses was possibly due to pigs that were not in the acute phase of the disease during the period when samples were collected, thus they did not shed the virus. The study found that a high percentage of pigs in Peninsular Malaysia were seropositive for H1N1 and H3N2. However, no isolates could be obtained to further characterise the virus to determine whether the virus strain was avian or human-related. This study revealed some of the deficiencies and issues with the existing disease surveillance that must be addressed to face the potential global influenza pandemic.